New perspectives on economic growth and technological innovation - Scherer, Frederic M. (Brookings Inst. Press, 1999)
"In this book, F. M. Scherer traces the evolution of economic growth theory from the Industrial Revolution to the present. Emphasizing technological change as the most crucial dynamic force for growth, Scherer analyzes early hypotheses that paid little attention to new technologies, follows the emergence of theories that increasingly emphasized technological change, and reviews the current state of economic growth theory. Pointing out a lack of solid microbehavioral foundations to support contemporary "new growth" ideas, Scherer then supplies some foundational "bricks" concerning financial investment and human capital and concludes by exploring the prospects for sustaining rapid growth into the next century."--BOOK JACKET.